Improving Problem Resolve Skill and Science Learning Result with Creating Worksheet Based on STEM - Desy Indriani; Hasruddin Hasruddin; Wildansyah Lubis (RIRAI Publisher, 2023)
The occurring problem, student worksheets have not been created truly in the learning process student worksheets used in the learning process only comes from. The student worksheets are not interactive, so that they have an impact on low learning outcomes and ability to solve science problems for fourth grade students at SDN 05 Binanga Dua. This research includes development research. This development research uses ADDIE development. The results of the development show that the manufacturing process produces the student worksheets on the STEM approach for grade IV students with a quality and valid. The results showed that the validation results of student worksheets feasibility test were based on the assessment of the three validators, namely the validation results of learning material experts of 88.23% with a very feasible classification, the validation results of linguists of 83.03% with a very feasible classification, the results of the presentation design expert validation of 93.75% with very decent qualifications. Furthermore, a feasibility test was carried out in small groups to obtain a data percentage of 84.6% and the trial was carried out again in the large group with a percentage result of 89.25% as a reinforcement of the feasibility assessment carried out by the homeroom teacher with a percentage result of 90%. So based on the validity of the student worksheets product, it shows very valid results which show that the student worksheets product is very feasible to be applied in learning activities.